Design and Implementation of a Secure QR Code-Based Attendance Management System for Higher Education - Emmanuel Ifeoluwa Oyerinde,; Felix Idepefo,; Francis Odo,; Akintoye Abraham Onamade,; Babajide Adeoti,; Oluwaseyi Adediran,; Opeyemi Adelowo,; Maryam Laminga,; Modupe Isaac,; Olanrewaju Oluwatobi Akinyosoye, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Attendance monitoring is a critical component of academic administration, directly influencing student participation, performance, and institutional accountability. Traditional manual methods, such as roll calls and registers, are inefficient, prone to errors, and vulnerable to fraudulent practices like proxy attendance. This paper presents the design and implementation of a secure QR code-based attendance management system tailored for higher education institutions. The proposed solution integrates a mobile application for students, a web interface for lecturers and administrators, and a cloud-enabled backend with PostgreSQL and AWS for secure data management. Advanced features, including dynamic QR codes, facial verification, and geolocation, are incorporated to ensure accuracy, prevent malpractice, and safeguard data integrity. Developed using an agile methodology, the system was evaluated through usability, performance, and security testing. Results indicate that the system reduced attendance marking time by more than 60% compared to manual methods, minimized recording errors, and improved transparency in reporting. User feedback highlighted increased efficiency and reduced administrative workload. The findings demonstrate the potential of QR code-based systems as cost-effective, scalable, and secure solutions for digital attendance management. Future work will explore the integration of learning management systems and predictive analytics for enhanced student engagement insights.
Keywords: QR Code; Attendance Management; Automation; Real-Time Tracking; Facial Verification; Higher Education